Analytical psychology and aesthetics of reception: possible dialogues (Psicologia USP, 2018)
This article briefly presents the field of Aesthetics of Reception and highlights the Jung’s writings related to art spectators, in order to establish bases for a dialogue between those texts and that still little-known discipline. The article brings up the particularities of the phenomena involved in the apprehension of works of art, considering, among others, Jungian notions of symbols, art as a compensation and the dynamic between consciousness and the unconscious. To ground the theoretical data, the study also introduces some passages that reveal Jung as a spectator of works of art. Finally, it takes a stand against the recent acts of censorship of contemporary works of art.